Myocardial Effects of Captopril and Lisinopril Addition to the Prime Solution and Cardioplegic Solution on Rat Heart under in vitro Perfusion Conditions (Annals of Medical Research, 2021)
None
Keywords: ACE inhibitors, Isolated rat heart, Coronary flow